PENGARUH GAYA BELAJAR DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS SMA - Firdaus Zulia Fatma, (Pendidikan Ekonomi, 2011)
The paper is intended to investigate whether learning styles and learning motivation had influence on the learning achievement. The study was associative research. The population was the tenth graders of SMAN I Mojokerto, consisting of 343 students clustered in eight classes, while the sample was 186 students. The result shows that learning styles and learning motivation partially and simultaneously had significant influence on the learning achievement. Thus, the suitability of learning styles and the existence of learning motivation had significant effect on the students learning achievement.